Photorelease of butyric acid from several (6-amino-2-oxo-2H-benzo[h]benzopyran-4-yl)methyl butyrate cages - Soares, Ana M. S. (2012)
Butyric acid is a naturally occurring short chain fatty acid involved in the regulatory mechanisms for gene expression known to promote markers of cell differentiation, apoptosis and cell growth control [1]. The poor absorption from the gastrointestinal tract of drugs containing ionisable polar groups like carboxylic acids can be ascribed to lipophilicity/solubility issues and it can be improved by masking the carboxyl group by forming derivatives through covalent linkage to suitable moieties. These pharmacologically inert chemical derivatives (prodrugs) are used to overcome common drawbacks such as low oral drug absorption, lack of site specificity, chemical instability, toxicity, and poor patient acceptance [2]. The accurate dosing of a drug at a specific location in vivo or in vitro can been attained by using photoactivable prodrugs, with a suitable photolabile group able to decompose rapidly upon photoirradiation, releasing the active drug. Recent reports in the field of prodrugs have proposed some examples of light as the triggering agent for the optimisation of drug delivery [3]. Considering the current interests of the authors on the synthesis and application of O and N heterocycles as photolabile protecting groups for the carboxylic and amine functions [4], it is now reported the synthesis of caged butyric acid 2 bearing aminated derivatives of 2-oxo-2H-benzo[h]benzopyran and the light triggered release of butyric acid 1 from the corresponding heterocyclic cages. The stability to irradiation of the ester bond between butyric acid and the caging group was evaluated in a photochemical reactor at 254, 300, 350 and 419 nm and uncaging data was acquired.